A (re)construção do modelo UTAUT 2 em contexto brasileiro - Nishi, Juliana Mayumi (2017)
The present work, characterized by being a descriptive and quantitative Survey, aimed to investigate the design of the Unified Theory of Acceptance Use of Technology 2 (UTAUT 2), by Venkatesh, Thong and Xu (2012), in context the use of smartphones. In order to achieve this goal, it was necessary to validate and adapt the model cross-culturally, as well as to examine the influence of the original moderating variables (age, gender and experience) and inclusions in this study (schooling, income and marital status). At the same time, the relationship between the moderating variables and the most commonly used applications in Brazil was analyzed. This way, the cross-cultural validation and adaptation of the model was verified through the modification of the seven stages of Borsa, Damásio and Bandeira (2012), and the questionnaire was, subsequently, applied to 1900 smartphone users, this sample has representatives from all the Brazilian states. The analysis was performed through descriptive and multivariate statistics with the use of Excel, SPSS and Amos softwares. The main results show that the UTAUT 2 model was validated in Brazil, however, different from the original model, since the construct "Facilitating Conditions" did not reach the necessary values, and its connection with Behavioral Intention is not possible, only with the Use Behavior. So, they were validated for the Brazilian model the relationship between Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, Price Value and Habit with Behavioral Intention and also the relation between the Habit to the Use Behavior. After the validation of the model, through the transformation of the moderating variables into binary, the influence of age, gender, experience, schooling, income and marital status on the constructs was verified, accepting eighteen of the forty sub-hypotheses proposed in this paper, and consequently, to state that all the proposed moderating variables are present in the Brazilian UTAUT 2 model. It is worth noting that Brazilians use few applications, the main ones being communication (WhatsApp), social (Facebook), tools (Google), media and videos (Youtube). And when we analyzed the higher frequencies of use, the results showed that the consumers who use the sixteen applications are characterized by being the youngest, female, with more experience, higher level of schooling, lower income and alone. In this way, understanding the behavior of the consumer in relation to the adoption of the technology allows to understand the impacts caused in the family, society, organizations and governments and allows the creation of applications, products and services and development of strategies of action able to attract more users concomitant with the responsibility of improving accessibility and digital inclusion.